Aspalathus linearis (Rooibos) and Agmatine May Act Synergistically to Beneficially Modulate Intestinal Tight Junction Integrity and Inflammatory Profile - L. Pretorius; C. Smith (MDPI AG, 2022)
In order to promote gastrointestinal health, significant increases in the prevalence of gastrointestinal disorders should be paralleled by similar surges in therapeutics research. Nutraceutical interventions may play a significant role in patient management. The current study aimed to determine the potential of Aspalathus linearis (rooibos) to prevent gastrointestinal dysregulation resulting from high-dose trace-amine (TA) exposure. Considering the substantial female bias in functional gastrointestinal disorders, and the suggested phytoestrogenicity of rooibos, the study design allowed for a comparison between the effects of an ethanol extract of green rooibos and 17β-estradiol (E2). High levels of ρ-tyramine (TYR) and agmatine (AGM), but not β-phenethylamine (PEA) or tryptamine (TRP), resulted in prostaglandin E2 (PGE2) hypersecretion, increased tight-junction protein (TJP; occludin and ZO-1) secretion and (dissimilarly) disrupted the TJP cellular distribution profile. Modulating benefits of rooibos and E2 were TA-specific. Rooibos pre-treatment generally reduced IL-8 secretion across all TA conditions and prevented PGE2 hypersecretion after exposure to both TYR and AGM, but was only able to normalise TJP levels and the distribution profile in AGM-exposed cells. In contrast, E2 pre-treatment prevented only TYR-associated PGE2 hypersecretion and TJP dysregulation. Together, the data suggest that the antioxidant and anti-inflammatory effects of rooibos, rather than phytoestrogenicity, affect benefits illustrated for rooibos.